Do Malaysian Listed Companies Mitigate Climate-change for Tax Planning? (Adakah Syarikat Tersenarai di Malaysia mengurangkan Perubahan Iklim untuk mengkaji Perancangan Cukai?) - Rayenda Khresna, Brahmana; Hui, Wei You (UKM Press (Penerbit UKM), 2017)
This research aims to examine the relationship between climate-change mitigation (CCM) and tax planning in Malaysian market. 248 listed companies and employing OLS with robust standard errors from six non-financial industries were examined from 2008 to 2014. The findings indicate a significant relationship between climate-change mitigation and tax planning. Furthermore, it is observed that climate-change mitigation has contributed negatively to tax planning. It shows that companies in Malaysian market use climate change mitigation in planning their taxation matter.